An interdisciplinary study on the human-baboon interface in Rooiels, South Africa - Mormile, Joselyn Elise (Department of Biological Sciences, 2025)
The ongoing transformation of natural habitat for urban land use has negatively affected most wildlife, but some species are capable of adapting to novel human-dominated landscapes and even exploit anthropogenic resources. Primates are particularly adept at exploiting resources in human-modified landscapes, and in Africa, chacma baboons (Papio ursinus) are arguably the most successful primate urban exploiters. However, these spaces present novel risks to their health and survival, and baboons can damage urban infrastructure, access food from gardens, vehicles, and houses, and pose health and safety risks to people and pets. Consequently, in the interests of both people and baboons, the latter are typically actively discouraged from entering urban areas through a variety of interventions. There is, however, a notable exception to this exclusionary approach with the small coastal village of Rooiels (Western Cape Province, South Africa) having opted to share their properties and village with the local baboon troop. This provided a unique opportunity to explore the local community's acceptance of baboons, and to investigate how, when given a choice, baboons use urban versus natural habitat. Additionally, the absence of formal deterrents in the urban area allows for a rare opportunity to explore how the use of an urban area may influence the ranging patterns, activity budget, diet, and life history of baboons. I explored the spatial and behavioural ecology of the Rooiels troop using GPS data and behavioural observations, respectively, and used questionnaires to understand the attitudes, emotions, and value orientations of the local community towards the troop. The troop had a small home range of 5.78 km2 with a clear preference for both low-lying land and the village. Within the village, the troop selected for developed properties and roads over undeveloped erven, and amongst the developed erven they preferred those with larger areas of grass, properties where residents did not actively deter them and where food was provisioned. Their diet in urban areas was comprised predominantly of natural fynbos vegetation, with grass from lawns a commonly consumed fallback food. Aside from some deliberate provisioning, which greatly influenced the troop's space use within the village, human-derived foods, including foods from houses, vehicles, and bins, comprised <4% of their overall diet but their access to these foods peaked during the summer holidays when visitors were prevalent. The troop's activity budget more closely mimicked those of provisioned primates, with the least amount of time spent feeding, and considerable time spent resting and socialising. However, fecundity was not greater than troops living in natural habitats and mortality was high with 20 deaths occurring during the research period, of which 75% were due to anthropogenic causes, namely vehicles and dogs. Most residents held a mutualist wildlife-value orientation, had a positive attitude towards baboons, and expressed low levels of fear and stress in response to baboon visits. Consequently, most residents were willing to share the urban space with baboons, and this acceptance increased over time, developing into a culture of community stewardship which encouraged responsible behavior aimed at enabling the existence of the troop in the village. Despite this, the high level of anthropogenic mortality poses a risk to the persistence of the troop and suggests that this, and other urban areas, act as an evolutionary trap for baboons. Thus, the application of this inclusion model to other urban areas is ill-advised, although promoting community education and awareness to promote wildlife responsible behaviour and so reduce the potential for negative interactions associated with occasional urban incursions, is strongly advised. This interdisciplinary study has shown that communities can learn to adjust their behaviour and attitudes to wildlife in a manner that promotes coexistence, but if space sharing has unintended negative impacts on wildlife, it should not be encouraged until those impacts are mitigated.